Resistance to the Implementation of the Badung Regency Government Policy Regarding Controlling Traders on the Edge of the Berawa Beach Area, Tibubeneng Village - Wibawa, I Made Wisnu Putra; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika, 2023)
This study describes the forms of resistance carried out by traders on the edge of Berawa Beach, Tibubeneng Village, against the implementation of Badung Regency Government policies. Tibubeneng Village is one of the tourism villages in Badung district, so that many problems regarding the scope of the tourism sector occur in this village. This research was conducted in Tibubeneng Village, especially in Berawa Beach, using descriptive qualitative research methods. The results of the research found that the implementation of the Badung Regency Government policy regarding controlling traders on the Berawa Beach met with resistance. With the existence of resistance, it cannot be separated from the factors behind the thoughts and actions of the traders, namely internal factors that can be seen from how the traders feel as local residents of Tibubeneng Village and the economic conditions of the traders, while external factors come from how the traders see opportunities, the strategic location of the area , and traders into a unified group. As for the forms of resistance carried out by traders on the edge of Berawa Beach, namely continuing to use semi-permanent buildings to sell, being indifferent, feeling afraid of traders until there is intervention, and as if accepting government policies. In James C. Scott's theory of resistance regarding the concept of everyday forms of resistance, namely resistance that is mediocre but occurs continuously. This concept can be seen in the forms of resistance from Berawa Beach traders.